Digital Transformation as the Subject of Discursive Analysis - Maciag, Rafal (IEEE International Conference on Industrial Informatics (INDIN), 2018)
Digital transformation (DT) is an important process that requires reflection but it is also transdisciplinary and dispersed. Discursive space (DS) is proposed as a way to unify this reflection. DS is based on the idea of dynamical space. Discourses move within it in the assumed dimensions. Because discourses are perceived as the realization of knowledge understood in a constructivist way, the DS is also a dynamic space of social knowledge, which is pragmatic, important e.g. for management. Social constructivism is justified as a dominant trend in the philosophy of technology as well as in the philosophy of knowledge and science. Discourse is interpreted as a complex phenomenon, based on the theory of Michel Foucault. DT is treated as the result of emergence in the space of discourses which supervene on the space of facts.